Information on Corona Virus Disease-19: Between the Public’s Right and State’s Interests - HAMZAH, Hamzah; YUSDIANTO, Yusdianto (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).15, 2020)
This study aims to describe the Public Rights and State Interests in managing information related to the Covid-19 outbreak filling public space. Civil society, cross-sectoral experts, the Government contributed opinions and information regarding the handling and response of Covid-19. Central to this public discourse is whether information about Covid-19 is public information as referred to in the provisions of Law No. 14 of 2008 concerning Public Information Openness (UU KIP). Or does it include information that is excluded on the grounds that there are a state's interests that are far more important than public information. This research is designed to be qualitative for this purpose and uses normative legal research methods. First research results, Covid-19 is a problem that involves many human lives. This dangerous and deadly virus outbreak threatens millions of people throughout the world. Therefore, the handling of Covid-19 concerns the interests or obligations of the state more precisely to protect its citizens. Second, the handling of Covid-19 requires the participation of all Indonesian people. Indonesia has a number of legal bases for implementing policies to address Covid-19. The management of information and the handling policies of Covid-19 are in the domain of state authority. All citizens must obey the Government's call and medical action to overcome Covid-19. Third, the experience of China which is a communist country turned out to be able to quickly overcome the Covid-19 outbreak. The obedience of its people and the unity of all elements and strengths that exist in the Chinese Government and medical personnel gave birth to a happy story free from Covid-19.